Ultrasonography and Computed Tomography Diagnostic Evaluation of Budd-Chiari Syndrome Based on Radical Resection Exploration Results. Issue 2 (June 2015) - Zhang, Li-Ming; Zhang, Guo-Yan; Liu, Yu-Lan; Wu, Jing; Cheng, Jin; Wang, Yi
Abstract : Objective: The current study used exploration during radical resection, which reveals the vascular lesion directly, as a criterion standard to evaluate and compare sonography and computed tomography (CT) diagnosis. Methods: A total of 70 patients (47 men and 23 women) with Budd-Chiari syndrome who underwent radical resection at Peking University People's Hospital between 2006 and 2012 were retrospectively examined. Sonography and CT were performed in all patients preoperatively. The lesions were classified into 6 groups on the basis of the intraoperative findings. Results: When compared with the surgical findings, sonography was significantly more accurate than CT (91.4% vs 77.1%, respectively; P = 0.035) in detecting membranous lesions with thrombosis of the inferior vena cava. Moreover, sonography was significantly more accurate than CT (80.0% vs 55.7%, respectively; P = 0.000) in detecting membranous lesions in hepatic vein openings and short-segment lesions (<1 cm) comprising thrombosis and fibrous tissue without the membrane in hepatic openings (87.1% vs 71.4%, respectively; P = 0.036). Conclusions: By using exploration during radical resection as the criterion standard to assess imaging modalities for Budd-Chiari syndrome, we found that sonography was advantageous over CT not only in detecting membranous lesions with inferior vena cava thrombosis but also in diagnosing lesions in hepatic vein openings.